NEUTRALIZE BACTERIAL ACTIVITY WITH ANATOMICAL EMBALMING SOLUTIONS - Dwi Martha Nur Aditya; Adhimas Setyo Wicaksono; Acik Afandi; Lady Theresa Adeodata; Lisa Thalia Mulyanata (Poltekkes Kemenkes Semarang, 2022)
Formaldehyde had some degree of toxicity in the human body as a cadaver preservation solution. Recent studies showed that moderate formaldehyde levels in cadavers could neutralize SARS-CoV-2. However, other effects of formaldehyde levels in the air are not yet known on bacteria. This study aims to determine the optimal level of formaldehyde that can be used to neutralize bacteria and is safe for humans. This study used a post-test control group design with formaldehyde level as the independent variable and bacterial colonization as the dependent variable. The results showed that the mean levels of formaldehyde with the bacterial colony respectively were P1 (1.378±0.716; 0.40±0.10), P2 (0.347±0.038; 1.40±0.10), P3 (0.137±0.006; 2.40 ±0.10), P4 (0.042±0.005; 3.32±0.09), and P5 (0.009±0016; 4.40±0.10). The statistical analysis results revealed a value of p0.05, which indicated that the higher the formaldehyde level, the higher the ability to neutralize bacterial activity. The study concluded the optimum level for neutralizing bacterial activity safe for humans is about 0347±0038 mg/m3.